Pembuatan Gagang Sendok Bayi Menggunakan Teknik Pengecoran Logam Metode Sand Casting - Muhammad Rayhan Nurfajrie; Fadly Tamimi; Sipahutar, David Adrianus; Aditya Surya Dinata; Hermanto, Tino (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
Metal casting is a manufacturing process that is widely used in industry. This research aims to examine the tin solder casting process using sand casting molds to make spoon handles. Soldering tin was chosen because it is often used in the electronics industry to connect components. The method used in this test is Sand Casting using a silica sand mold. The silica sand molds used include disposable molds or Expandable Molds. The results of tin solder casting show that the silica sand sand casting mold produces baby spoon handle products. This research shows that casting tin solder using silica sand sand casting molds produces size error defects which result in dimensional changes between the sample object and the casting product. These dimensional changes indicate that the dimensions of the casting product are smaller than the sample object. Apart from that, there are also holes in the form of air cavities or porosity experienced by casting products.